Protein moonlighting in iron metabolism: glyceraldehyde-3-phosphate dehydrogenase (GAPDH). (17th November 2014) - Boradia, Vishant Mahendra; Raje, Manoj; Raje, Chaaya Iyengar
Abstract : Iron is essential for the survival of both prokaryotic and eukaryotic organisms. It functions as a cofactor for several vital enzymes and iron deprivation is fatal to cells. However, at the same time, excess amounts of iron are also toxic to cells due to the formation of free radicals via the Fenton reaction. As a consequence of its double-edged behaviour, the uptake and regulation of iron involves an intricate balance of acquisition, trafficking, recycling and shuffling between various tissues and organs. This is accomplished by differential regulation of genes involving numerous proteins and enzymes. Several of the proteins identified in these processes, such as glyceraldehyde-3-phosphate dehydrogenase (GAPDH), aconitase and lactoferrin (Lf), possess multiple functions within the cell. Such proteins are referred to as moonlighting or multifunctional proteins, whereby proteins initially thought to possess a single well-established function have subsequently been discovered to exhibit alternative functions. In many cases, these multiple functions are conserved across species.